Determination of Predictive Factors of Choledocholithiasis in Cases of Acute Biliary Pancreatitis - Marta Horakova; Iveta Vadovicova (Communications - Scientific letters of the University of Zilina, 2011)
Choledocholithiasis (bile duct stones) may bring about biliopancreatic obstruction that eventually develops into acute biliary pancreatitis, which could become a serious, life threatening disease. Because stones have the propensity to move spontaneously from the bile duct, it is allimportant to determine as accurately as possible, whether biliopancreatic obstruction is still present or not. The aim is to avoid, wherever possible, any invasive and costly diagnostic and therapeutic procedures while preventing serious risk to the patient. In this paper, by retrospective analysis of patients with acute biliary pancreatitis, we examine laboratory and other parameters, obtained by quick and easy to implement non-invasive methods, for to determine predictive factors of biliopancreatic obstruction. Our results indicate that the definite predictive parameter for choledocholithiasis is previous cholecystectomy and the dilation of the bile duct. Supporting predictive factors are bilirubin and alanine aminotransferase.